Benign Envy and Prosocial Personality Among Indonesian Undergraduates: Affective and Moral Dimensions - Nurfitriany Fakhri; Mufliha Chaerati; Basti Tetteng (Nusantara Journal of Behavioral and Social Science, 2026)
Prosocial personality is a stable disposition to help others, grounded in empathy, moral reasoning, and social responsibility. Benign envy is a constructive emotion arising from upward social comparison that motivates self-improvement through emulating admired others without hostility. Unlike malicious envy, which is directed at pulling others down, benign envy involves admiration and aspiration. The empirical association between these constructs remains underexplored, particularly in non-Western contexts. This study examined their association in Indonesian undergraduates. A total of 348 students (70.7% female; aged 18–25 years) from 21 universities in Makassar participated in this cross-sectional correlational study. Prosocial personality was assessed using an Indonesian adaptation of the Prosocial Personality Battery, and benign envy was measured with a researcher-developed scale based on Lange and Crusius (2015). Spearman’s rank-order correlation was used for analysis. Results indicated a modest but statistically significant positive association between prosocial personality and benign envy (ρ = .177, p = .001). Benign envy was positively associated with sympathetic responsiveness (ρ = .268), empathic concern (ρ = .218), and moral reasoning (ρ = .151), and negatively associated with personal distress (ρ = −.146). Applying Bonferroni correction (α = .006), no significant associations were found for perspective taking, other-orientation, or social responsibility. These preliminary findings suggest that benign envy may be associated with the affective and moral components of prosocial personality, with implications for positive psychology and character education in collectivist settings. Abstrak: Kepribadian prososial adalah kecenderungan stabil untuk membantu orang lain, yang berlandaskan empati, penalaran moral, dan tanggung jawab sosial. Iri hati yang baik adalah emosi konstruktif yang muncul dari perbandingan sosial ke atas yang memotivasi peningkatan diri melalui meniru orang lain yang dikagumi tanpa permusuhan. Tidak seperti iri hati yang jahat, yang diarahkan untuk menjatuhkan orang lain, iri hati yang baik melibatkan kekaguman dan aspirasi. Hubungan empiris antara konstruk-konstruk ini masih kurang dieksplorasi, khususnya dalam konteks non-Barat. Studi ini meneliti hubungan mereka pada mahasiswa sarjana di Indonesia. Sebanyak 348 mahasiswa (70,7% perempuan; usia 18–25 tahun) dari 21 universitas di Makassar berpartisipasi dalam studi korelasional lintas-seksional ini. Kepribadian prososial diukur menggunakan adaptasi Indonesia dari Prosocial Personality Battery, dan iri hati diukur dengan skala yang dikembangkan peneliti berdasarkan Lange dan Crusius (2015). Korelasi peringkat Spearman digunakan untuk analisis. Hasil penelitian menunjukkan adanya hubungan positif yang moderat namun signifikan secara statistik antara kepribadian prososial dan rasa iri yang baik (ρ = 0,177, p = 0,001). Rasa iri yang baik berhubungan positif dengan respons simpatik (ρ = 0,268), kepedulian empatik (ρ = 0,218), dan penalaran moral (ρ = 0,151), serta berhubungan negatif dengan tekanan pribadi (ρ = −0,146). Dengan menerapkan koreksi Bonferroni (α = 0,006), tidak ditemukan hubungan yang signifikan untuk pengambilan perspektif, orientasi terhadap orang lain, atau tanggung jawab sosial. Temuan awal ini menunjukkan bahwa rasa iri yang baik mungkin berhubungan dengan komponen afektif dan moral dari kepribadian prososial, dengan implikasi bagi psikologi positif dan pendidikan karakter dalam lingkungan kolektivis.